EVALUATION OF THE SAMPLING DESIGN ADOPTED BY THE CENTRAL MARINE FISHERIES RESEARCH INSTITUTE FOR ESTIMATING MARfNE FISH PRODUCTION OF INDIA - Kutty, M Krishnan; Nair, A K Kesavan; Quasim, S Z (Indian Journal of Fisheries, 2011)
The sampling design used by the Central Marine Fisheries Research Institute, for collecting the catch data of sea fish in India is based on the procedure of stratification in space and time. The coastline is divided into different zones and one zone and a cluster of 10 days are taken as the sizes of a space-time stratum. Generally one survey staff is allotted to each zone. Certain limitations in the sampling system seem at present inevitable because of the fishing conditions under which the survey work is being carried out.